Global climate change and Indian agriculture: impacts, adaptation and mitigation - Aggarwal, P K (The Indian Journal of Agricultural Sciences, 2008)
Inter-Governmental Panel on Climate Change has shown that the earth temperature has increased by 0.74 degree C between 1906 and 2005 due to increase in anthropogenic emissions of greenhouse gases. By the end of this century, temperature increase is likely to be 1.8-4.0 degreee C. This would lead to more frequent hot extremes, floods, droughts, cyclones and gradual recession of glaciers, which in turn would result in greater instability in food production. It is estimated that crop production loss in India by 2100 AD could be 10-40% despite the beneficial effects of higher C02 on crop growth. We could lose 4-5 million tonnes of wheat (Triticum aestivum L. emend. Fiori & Paol.) with every rise of 1 degree C temperature. Dynamics of pests and diseases will be significantly altered. Agriculture contributes 28% of the Indian greenhouse gases emissions, primarily due to methane emission from rice (Oryza sativa L.), enteric fermentation in ruminant animals, and nitrous oxides from application of manures and fertilizers to the soils. Potential approaches to reduce these emissions include mid-season drainage or alternate drying in rice, approaches to increase N-use efficiency and soil carbon, and improvement in livestock diet. Simple adaptation strategies, such as change in planting dates and varieties could help in reducing impacts of climate change to some extent. Additional strategies for increasing our adaptive capacity include development of adverse climate-tolerant genotypes and land-use systems, providing value-added climatic risk management services to farmers, and improved land-use policies and risk management though early warning system and crop-weather insurance.